(untitled) (PÓS: Revista do Programa de Pós-graduação em Artes da EBA/UFMG, 2020)
This paper presents a sample of art education experiences that I have been privileged to explore over 40 years. This has involved developing rationales that were required to apply to the new technologies emerging in art education in 1985. My research in this area included media workshops in England, Europe and South America. The new ‘cultures’ of communication and new technologies in 21st century continue to expand our understanding of both the universe and the diverse ecosystems on our planet. We live in the age of interdisciplinary practice, which provides new opportunities for artists to collaborate with scientists and mathematicians.